2020
DOI: 10.3389/fcell.2020.00466
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functions of ATG8 Family Proteins in Plant Autophagy

Abstract: Autophagy is a major degradation process of cytoplasmic components in eukaryotes, and executes both bulk and selective degradation of targeted cargos. A set of autophagy-related (ATG) proteins participate in various stages of the autophagic process. Among ATGs, ubiquitin-like protein ATG8 plays a central role in autophagy. The ATG8 protein is conjugated to the membrane lipid phosphatidylethanolamine in a ubiquitin-like conjugation reaction that is essential for autophagosome formation. In addition, ATG8 intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 115 publications
3
54
0
1
Order By: Relevance
“…In plants, the number of Atg8 orthologs varies from 1 in algae to 22 in angiosperms [74]; however, the diversity of plant Atg8 proteins could be significantly higher because of multiple gene duplications in order to adapt to various adverse conditions where Atg8 proteins play a crucial role [75]. The plant Atg8 proteins also reveal significant selectivity in interaction with their interaction partners, originated from the sequence difference between Atg8 isoforms in different species [76].…”
Section: Lessons From Alignment Of Atg8 Family Membersmentioning
confidence: 99%
“…In plants, the number of Atg8 orthologs varies from 1 in algae to 22 in angiosperms [74]; however, the diversity of plant Atg8 proteins could be significantly higher because of multiple gene duplications in order to adapt to various adverse conditions where Atg8 proteins play a crucial role [75]. The plant Atg8 proteins also reveal significant selectivity in interaction with their interaction partners, originated from the sequence difference between Atg8 isoforms in different species [76].…”
Section: Lessons From Alignment Of Atg8 Family Membersmentioning
confidence: 99%
“…These results illustrated a higher similarity with homology proteins in tea plant than in Arabidopsis , and CsATG8e showed more sequence similarity to ATG8c in both Arabidopsis and Camellia sinensis . Based on the amino acid sequences, ATG8 proteins can be divided into three groups: clade I (a), clade I (b) and clade II [ 33 ]. However, according to our phylogenetic analysis of CsATG8s ( Figure 2 ), no clear classification was found for CsATG8s in tea plant.…”
Section: Resultsmentioning
confidence: 99%
“…In crops like rice [ 42 , 49 , 50 ] and soybean [ 51 ], a number of members in the ATG8 subfamily have been shown to participate in N utilization. Previous studies have shown that the ATG9 complex and ubiquitin-like conjugation pathways are indispensable in the process of autophagy and NBR1 is a typical receptor for selective autophagy [ 25 , 33 ]. In this study, the expressions of AtATG9 , AtNBR1 and 9 genes in ubiquitin-like conjugation pathways were found to be upregulated in OE lines versus WT ( Figure 6 a,d), indicating the enhanced autophagy in CsATG8e transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the expression of the BnATG8 subfamily under all abiotic stresses was higher than other subfamilies, which is the following results obtained in Arabidopsis [ 38 ], foxtail millet [ 50 ], and wheat [ 38 , 50 , 71 ]. ATG8 is a ubiquitin-like protein conjugated to phosphatidylethanolamine (PE) catalyzed by ATG7, ATG3, and ATG12-ATG5 complex [ 72 ]. ATG8-PE complex is essential for autophagosome formation through the membrane connection and remodeling [ 73 ].…”
Section: Discussionmentioning
confidence: 99%